Faktor-faktor penunjang produk nano spray dengan metode factor analysis - Ai Nurhayati (Universitas Insan Cendekia Mandiri, 2021)
This study aims to identify supporting factors in the selection of nano spray products. This study uses factor analysis method through SPSS statistics software. The results showed that there are two main factors that support nano spray products, namely tool and content factors. Keywords: Factor analysis, Nano spray, SPSS, Statistics